Impact of Oil Price, CO2 Emissions and Renewable Energy Consumption on Socio-Economic Development: Asymmetric Evidence from Kazakhstan - Dildebayeva, Zhulduz; Kakizhanova, Tolkyn; Andabayeva, Gulmira; Askarova, Zhanar; Oralbayeva, Zhanar (International Journal of Energy Economics and Policy, 2025)
Preserving the environment while promoting socioeconomic growth is becoming increasingly important in the modern world. After all, the generation of energy causes the world climate to deteriorate. Alternative approaches to social and economic growth and damage reduction are therefore always pertinent. This study aims to evaluate how socioeconomic growth is affected by significant indicators including oil prices, CO2 emissions, and the use of renewable energy. Socioeconomic development metrics were the GDP per capita and the Human Development Index. Nonlinear autoregressive distributed lag (NARDL) is the approach employed, and the data spans the years 1992–2021. The model results revealed that all indicators have a significant impact on the socio-economic situation, and it was observed that the results of previous years also have an impact on the next year. CO2 emissions have a negative impact on the human development index in the short term and a negative impact in the long term. The positive impact of all other indicators on socio-economic development in the long term can be explained by the fact that the economy of Kazakhstan is oriented towards the export of raw materials, especially the mining and oil and gas sectors. Some policy implications presented in the final section.